Anthropocentrism in the graphic novel Black Beauty - Rajendra, Thusha Rani; Taib, Fauziah (Journal of Modern Languages, 2017)
This article explores the link between linguistic formations and socially organised meanings in a graphic novel of the adapted classic genre. Focus has been placed specifically on its verbal text contained in speech bubbles and captions. Using Halliday’s (1994) Systemic Functional Linguistics (SFL) framework of the ideational metafunction that employs transitivity, the article discusses how the ideology of anthropocentrism and the theme of mistreatment of animals are represented in the verbal layout of the novel Anna Sewell’s Black Beauty. In addition, a typography analysis of onomatopoeic words will also be examined, as that complements the representation of the ideology and themes. The analysis of the data indicates that the linguistic choices of the author support the construction of the ideology and themes. The main significance of the study is that it highlights how discursive choices that represent the inner and outer experiences are constructed in the panels of Black Beauty.